Targeting nuclear transporters in cancer: Diagnostic, prognostic and therapeutic potential. Issue 4 (11th March 2016) - Stelma, Tamara; Chi, Alicia; van der Watt, Pauline J.; Verrico, Annalisa; Lavia, Patrizia; Leaner, Virna D.
Abstract: The Karyopherin superfamily is a major class of soluble transport receptors consisting of both import and export proteins. The trafficking of proteins involved in transcription, cell signalling and cell cycle regulation among other functions across the nuclear membrane is essential for normal cellular functioning. However, in cancer cells, the altered expression or localization of nuclear transporters as well as the disruption of endogenous nuclear transport inhibitors are some ways in which the Karyopherin proteins are dysregulated. The value of nuclear transporters in the diagnosis, prognosis and treatment of cancer is currently being elucidated with recent studies highlighting their potential as biomarkers and therapeutic targets. © 2016 IUBMB Life, 68(4):268–280, 2016